2023
DOI: 10.1021/acs.energyfuels.3c00309
|View full text |Cite
|
Sign up to set email alerts
|

MOF-on-MOF Composites with UiO-66-Based Materials as Photocatalysts for the Overall Water Splitting under Sunlight Irradiation

Abstract: There is a large interest in the sustainable conversion of H 2 O into H 2 and O 2 , assisted by sunlight. In recent times, metal−organic frameworks (MOFs) have evolved as promising photocatalysts for this reaction. In the present study, a number of novel MOF-on-MOF composites possessing UiO-66 topologies, namely UiO-66(Ce), UiO-66(Zr)-NH 2 , UiO-66(Zr)-NH 2 @UiO-66(Ce), and UiO-66(Ce)@UiO-66(Zr)-NH 2 , are prepared, and their photocatalytic activity is examined in the overall water splitting under simulated su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 59 publications
(105 reference statements)
1
14
0
Order By: Relevance
“…As evident from Figure S1 of the Supporting Information, the sharp peak with the corresponding g = 2.05 can be assigned to oxygen vacancies. 38,39 It is revealed that oxygen vacancies can absorb anions to accelerate the dissociation of Li salt, yielding a higher lithium-ion transference number and, thus, higher effective ionic conductivity. 40 After the addition of UiO-66 into the polymer matrix, the crystallinity of the solid polymer electrolyte decreases and no new crystalline peaks appear in the curve of UPH-SPE, resulting in more amorphous regions in UPH-SPE.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As evident from Figure S1 of the Supporting Information, the sharp peak with the corresponding g = 2.05 can be assigned to oxygen vacancies. 38,39 It is revealed that oxygen vacancies can absorb anions to accelerate the dissociation of Li salt, yielding a higher lithium-ion transference number and, thus, higher effective ionic conductivity. 40 After the addition of UiO-66 into the polymer matrix, the crystallinity of the solid polymer electrolyte decreases and no new crystalline peaks appear in the curve of UPH-SPE, resulting in more amorphous regions in UPH-SPE.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Researchers have shown more interest in using MOFs as precursors to create catalysts with specific structures and chemical components rather than utilizing them in their pristine form or as composite MOFs. This approach has shown promise in enhancing the electrocatalytic activity of MOFs as HER catalysts through structural alteration. One advantage of these MOFs is their ability to overcome common drawbacks of other MOFs, such as poor inherent conductivity and constancy in electrolytes.…”
Section: Mofs Derivatives For Efficient Her Electrocatalysismentioning
confidence: 99%
“…Hence, monolithic formations are more conducive to keeping them stable during the reaction without a decrease in activity caused by weight loss and are beneficial to the recycling of materials. Next, industrial catalysis based on the direct heterogeneous catalysis of MOFs is introduced …”
Section: Applications Of Monolithic Mofsmentioning
confidence: 99%